Passion fruit waste in diets for quail in the laying phase (Acta Scientiarum. Animal Sciences, 2020)
It was aimed to evaluate the effect of including the waste from passion fruit pulp extraction in diets for Japanese quail in the laying phase on their production performance and egg quality. A total of 280 female quail were distributed into five treatments with eight replicates and seven birds per cage. Treatments consisted of 0, 2, 4, 6, or 8% inclusion of passion fruit waste in the diet. The experiment began with quail at 70 days of age and lasted 63 days, with performance evaluated every 21 days and egg quality in the last two days of each cycle. There was no difference between the treatments for feed intake, body weight, specific gravity, or eggshell thickness. However, a decreasing linear regression was obtained for feed intake with the inclusion of the waste, while a quadratic response was show by egg production, weight and parts of the egg. Inclusion of up to 6% passion fruit waste in diets for quail is recommended to maintain the indices in relation to control treatment. However, the best values for egg-laying rate and for the weights of egg, albumen, yolk, and shell are obtained with 2.5 to 3.5% inclusion of passion fruit waste.